Ferenczi's anticipation of the traumatic dimension of language: A meeting with Lacan (2015)
The work of Sándor Ferenczi anticipates various challenges of contemporary psychoanalysis - clinical, technical, and theoretical. Among the most novel is his elaboration of the concept of trauma. Ferenczi's 1930s writings were mostly read by the psychoanalysts of his time, including Freud, as a return to Freud's seduction theory. Nevertheless, in Ferenczi, there is an innovation that distinguishes him from Freud. Although today's psychoanalytic community expresses a growing interest in Ferenczi's trauma theory, the field pays less attention to his focus on the traumatic dimension of language itself and the effects language has on the subject. In fact, Ferenczi's later work uniquely explores the relationship between trauma and language. In part, what makes Ferenczi's trauma theory unique is that it anticipates Jacques Lacan's work on the traumatic dimension of language, which the French psychoanalyst referred to in his final theoretical production through the concept of lalangue. © William Alanson White Institute of Psychiatry, Psychoanalysis and Psychology and the William Alanson White Psychoanalytic Society.